Pengaruh E-Commerce dan Kualitas Sumber Daya Manusia Terhadap Kinerja Keuangan UMKM - Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Daniel Collyn; Suci Etri Jayanti. S; Murbanto Sinaga; Sri Winda Hardiyanti Damanik (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Currently, many MSMEs are struggling to develop even though they are the backbone of the Indonesian economy. On the other hand, improving the sustainable financial performance of MSMEs is believed to be one of the main keys for MSMEs to upgrade and survive. Therefore, this study aims to analyze the effect of e-commerce and human resource quality on the financial performance of MSMEs. This research was conducted on 38,343 MSME players registered in the SIMDAKOP UMKM application in Medan City in 2022. The research sample amounted to 100 people selected using simple random sampling technique. The type of data used is primary data. The data was collected using a questionnaire distributed to selected respondents. The research data were analyzed using multiple linear regression analysis method with SPSS 26 software. The results of the analysis show that e-commerce has a positive and significant effect on financial performance of MSMEs. HR quality also has a positive and significant effect on financial performance of MSMEs. E-commerce and HR quality simultaneously have a significant effect on the financial performance of MSMEs. The implication of this research is a guideline for MSMEs in making business strategy decisions to ensure sustainable financial performance of MSMEs, which will help MSMEs to upgrade and survive in competition.